2011
DOI: 10.1002/asi.21489
|View full text |Cite
|
Sign up to set email alerts
|

Hip and trendy: Characterizing emerging trends on Twitter

Abstract: Twitter, Facebook, and other related systems that we call social awareness streams are rapidly changing the information and communication dynamics of our society. These systems, where hundreds of millions of users share short messages in real time, expose the aggregate interests and attention of global and local communities. In particular, emerging temporal trends in these systems, especially those related to a single geographic area, are a significant and revealing source of information for, and about, a loca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
155
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 249 publications
(162 citation statements)
references
References 279 publications
(303 reference statements)
2
155
0
Order By: Relevance
“…Furthermore, as Naaman et al (2011) observed, the endogenous or exogenous nature of tweets also affect their circulation. For example, tweets like 16 and 17, which explicitly reference a Brazilian politician, circulated widely among Brazilian Portuguese-language users, but did not seem to be popular among users who tweeted in other languages.…”
Section: Restrictions On the Circulation Of Memesmentioning
confidence: 87%
“…Furthermore, as Naaman et al (2011) observed, the endogenous or exogenous nature of tweets also affect their circulation. For example, tweets like 16 and 17, which explicitly reference a Brazilian politician, circulated widely among Brazilian Portuguese-language users, but did not seem to be popular among users who tweeted in other languages.…”
Section: Restrictions On the Circulation Of Memesmentioning
confidence: 87%
“…Moreover, the retweet mechanism on Twitter enables people to share messages with their followers and provides people a channel to endorse their perspectives regarding specific topic (Borondo, Morales, Losada, & Benito, 2012). A retweet commonly use the "RT @username" text as prefix to credit the original poster (Naaman et al, 2011). Thus the users with the greatest number of retweets are also identified as the influencers on Twitter.…”
Section: Data Collection and Methodologymentioning
confidence: 99%
“…At each people in the network, the probability of transmission and the number of connections to other people determines how fast and how far the information spreads. Twitter supports a hashtag annotation format [10] so that users can indicate what their posted messages are about. This general "topic" of a tweet is, by convention, indicated with the hash sign, #.…”
Section: Introductionmentioning
confidence: 99%
“…Topics that are very popular in real time are called "trends" on Twitter. A trend on Twitter [10] consists of one or more terms and a time period, such that the volume of messages posted for the terms in the time period exceeds some expected level of activity .Trends were initially created from the most used hashtags, but now Twitter also shows keywords as part of the trends. Twitter trends are dynamic and change depending on the tweets being created at real time.…”
Section: Introductionmentioning
confidence: 99%